Qualitative Research Methodology in Social Sciences (International Journal of Scientific Research and Management (IJSRM), 2023)
The objective of this study is to provide a guide to qualitative research methodology in social sciences. It is the result of the observation that research in Management Sciences in most Universities in Cameroon is still dominated by the quantitative approach supported by economists who handle most research methodology courses. In an environment of oral tradition and the difficulties to have access to data, emphasising purely quantitative research may leave aside many aspects of the environment and several areas of human behaviour that make its specificities. Therefore, there is a need to generalise the use of qualitative research to enable researchers to always have a good insight into phenomena not yet clarified before thinking of any generalisation which is the main objective of quantitative research: this gives room to the contextualisation of research which results can easily be applied in its context, thus, enhancing development.